Gender differences in mental health help-seeking behaviour in Bangladesh: findings from a cross-sectional online survey - Mohammad Tajul Islam; Zunayed Al Azdi; Saiful Islam Saif; Sayedul Ashraf Kushal; Lubaba Maaz; Shusama Reza; Sharmeen Yasmeen; Mainul Alam Chaklader; Yahia Md Amin (BMJ Open)
Background Mental health disparities persist as a pressing public health concern globally. Gender disparities in mental health are evident, with women disproportionately affected by conditions such as depression and anxiety. Despite the apparent need, studies from Bangladesh indicate that women are less likely to seek mental healthcare compared with men.Objective This study aims to investigate gender differences in mental health help-seeking behaviour in Bangladesh.Methods A cross-sectional online survey was conducted from 15 to 30 October 2021, targeting individuals with perceived mental health problems through the Facebook page of LifeSpring, a mental health and well-being organisation based in Bangladesh. Data (n=3031; women: 2140; men: 891) were collected using the JotForm online survey tool and analysed using descriptive statistics, bivariate analyses and multinomial logistic regression.Results The majority of participants were female (70.6%), aged between 18 and 34 years (87.3%), and from urban areas (85.4%). Overall, 28.4% received non-professional help, with females at 30.9% and males at 22.3%. Additionally, 22.9% received help from professionals, with females at 20.8% and males at 28.1%. Notable disparities were observed in mental health help-seeking behaviour between genders. While females exhibit higher odds of seeking non-professional support (OR 1.49, 95% CI 1.21 to 1.84, p value <0.001), they have lower odds of obtaining professional assistance compared with males (OR 0.70, 95% CI 0.56 to 0.86, p value 0.001). Factors such as stigma, financial constraints and marital status significantly influenced help-seeking behaviours.Conclusion This study contributes to our understanding of gender disparities in mental healthcare utilisation in Bangladesh, highlighting the need for gender-sensitive approaches in mental healthcare service delivery.